The Temperature Profile for The Innovative Design of the Perforated Fin - Al-Saddy, Hisham; Soylemez, Mehmet (International Journal of Renewable Energy Development, 2016)
The development of the perforated fin had proposed in many studies to enhance the heat transfer from electronic pieces. This paper presents a novel derivative method to find the temperature distribution of the new design (inclined perforated) of the pin fin. Perforated with rectangular section and different angles of inclination was considered. Signum Function is used for modeling the variable heat transfer area. Set of parameters to handle the conduction and convection area were calculated. Degenerate Hypergeometric Equation (DHE) was used for modeling the Complex energy differential equation and then solved by Kummer’s series. In the validation process, Ansys 16.0-Steady State Thermal was used. Two geometric models were considered. The big reliability of the presented model comes from the high agreement of the validation results about (0.25%). The results show the increase of the inclination leads to the enhancement of the temperature difference and heat transfer ratio. Improved of Heat transfer ratio is ranging from 13% to 50%.Article History: Received June 12th 2016; Received in revised form August 6th 2016; Accepted August 24th 2016; Available onlineHow to Cite This Article: Jasim, H.H and Soylemez, M.S. (2016). The temperature profile for the innovative design of the perforated fin. Int. Journal of Renewable Energy Development, 5(3), 259-266http://dx.doi.org/10.14710/ijred.5.3.259-266